Plaque Removal By Three Types Of Toothbrushes In Fıxed Orthodontıc Patıents - Selim Arıcı; Tamer Türk; Ahu Cezayirli (Galenos Yayinevi, 1998)
This study investigated plaque removal effects of three different types of toothbrushes in 30 female patients having fixed appliances. All patients were disclosed at the start and a modified PI index was used to evaluate the amount of plaque on the labial surfaces of maxillary and mandibular anterior teeth. Group 1 brushed with an orthodontic toothbrush prior to interdental toothbrush. Group 2 brushed only with an orthodontic toothbrush. Group 3 brushed only with a conventional toothbrush. The patient was then redisclosed at the same visit and retained plaque was scored. One-way ANOVA revealed a statistically significant difference in the effectiveness of plaque removal among three groups. It is concluded that orthodontic toothbrush when used with interdental toothbrush is significantly better at removing plaque deposits from fixed appliance patients than either orthodontic toothbrush or conventional toothbrush alone.